The Relationship Between Academic Stress and Menstrual Cycle Disorders in Adolescents - Indriani, Vivi; Puspasari, Jehan; Rahmawati, Veronica Yeni (Yayasan Ahmad Mansyur Nasirah, 2025)
Adolescence is a developmental phase that is highly vulnerable to physiological and psychological changes, including disturbances in the menstrual cycle. Academic stress is suspected to be one of the contributing factors to menstrual irregularities among female students. The purpose of this study was to analyze the relationship between academic stress and menstrual cycle disorders in adolescents. This research employed a quantitative design with a cross-sectional approach and total sampling technique, involving 136 first-year female students. The study was conducted at STIKes RS Husada Jakarta during April–May 2025. Academic stress was measured using the 42-item Depression Anxiety Stress Scale (DASS) with a scoring range of 0–3. The results showed that 93 respondents (68.4%) experienced severe to very severe stress, and 87 respondents (64.0%) had abnormal menstrual cycles. The Chi-Square test yielded a p-value < 0.001, indicating a significant relationship between academic stress and menstrual cycle disorders. These findings emphasize that academic stress has a strong influence on adolescents’ menstrual patterns and should be a priority for educational institutions when strengthening stress management programs and psychosocial support to maintain reproductive health. In conclusion, the higher the level of academic stress, the greater the risk of menstrual cycle disturbances among adolescents.